Comprehensive Study of the Current-Induced Spin–Orbit Torque Perpendicular Effective Field in Asymmetric Multilayers - Baoshan Cui; Zengtai Zhu; Chuangwen Wu; Xiaobin Guo; Zhuyang Nie; Hao Wu; Tengyu Guo; Peng Chen; Dongfeng Zheng; Tian Yu; Li Xi; Zhongming Zeng; et al. (Nanomaterials, 2022)
The spin–orbit torques (SOTs) in the heavy metal (HM)/ferromagnetic metal (FM) structure hold promise for next-generation low-power and high-density spintronic memory and logic applications. For the SOT switching of a perpendicular magnetization, an external magnetic field is inevitable for breaking the mirror symmetry, which is not practical for high-density nanoelectronics applications. In this work, we study the current-induced field-free SOT switching and SOT perpendicular effective field (<semantics><msubsup>Hzeff</msubsup></semantics>) in a variety of laterally asymmetric multilayers, where the asymmetry is introduced by growing the FM layer in a wedge shape. We show that the design of structural asymmetry by wedging the FM layer is a universal scheme for realizing field-free SOT switching. Moreover, by comparing the FM layer thickness dependence of (<semantics><msubsup>Hzeff</msubsup></semantics>) in different samples, we show that the efficiency (β =<semantics><msubsup>Hzeff</msubsup></semantics>/J, J is the current density) is sensitive to the HM/FM interface and the FM layer thickness. The sign of β for thin FM thicknesses is related to the spin Hall angle (θSH) of the HM layer attached to the FM layer. β changes its sign with the thickness of the FM layer increasing, which may be caused by the thickness dependence of the work function of FM. These results show the possibility of engineering the deterministic field-free switching by combining the symmetry breaking and the materials design of the HM/FM interface.